2021
DOI: 10.3389/fimmu.2021.614320
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of Targeting Heat Shock Protein 70 by Immunization or Antibodies in Experimental Skin Inflammation

Abstract: Heat shock proteins (Hsp) are constitutive and stress-induced molecules which have been reported to impact innate and adaptive immune responses. Here, we evaluated the role of Hsp70 as a treatment target in the imiquimod-induced, psoriasis-like skin inflammation mouse model and related in vitro assays. We found that immunization of mice with Hsp70 resulted in decreased clinical and histological disease severity associated with expansion of T cells in favor of regulatory subtypes (CD4+FoxP3+/CD4+CD25+ cells). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…In the past, molecular mimicry hypothesis suggested that the immune response originally directed to the bacterial Hsps may be re-directed towards their human counterparts and in this way promote development of autoimmune reactions (Albani et al 1995 ). While immune cross-reactions between foreign and self-antigens were experimentally confirmed in the case of Hsp40, Hsp60, or Hsp70 chaperones (Kotlarz et al 2013 ; van Eden et al 2017 ), clinical consequences of such immune cross-reactions have brought ambiguous outcomes (Tukaj and Kaminski 2019 ; Tukaj et al 2021 ; van Eden et al 2017 ). Information on a potential contribution of the bacterial Hsp90 (HtpG) in autoimmunity and the immune cross-reactions between HtpG and human Hsp90, however, is generally lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, molecular mimicry hypothesis suggested that the immune response originally directed to the bacterial Hsps may be re-directed towards their human counterparts and in this way promote development of autoimmune reactions (Albani et al 1995 ). While immune cross-reactions between foreign and self-antigens were experimentally confirmed in the case of Hsp40, Hsp60, or Hsp70 chaperones (Kotlarz et al 2013 ; van Eden et al 2017 ), clinical consequences of such immune cross-reactions have brought ambiguous outcomes (Tukaj and Kaminski 2019 ; Tukaj et al 2021 ; van Eden et al 2017 ). Information on a potential contribution of the bacterial Hsp90 (HtpG) in autoimmunity and the immune cross-reactions between HtpG and human Hsp90, however, is generally lacking.…”
Section: Discussionmentioning
confidence: 99%
“…no. ADI-SPP-770; Enzo Life Science) or previously purified recombinant Hsp70 (Tukaj et al 2021 ) proteins at a concentration of 0.5 μg/ml in 0.05 M bicarbonate buffer at 4°C overnight. The wells were blocked with 1% bovine serum albumin (BSA) in phosphate-buffered saline (PBS) at room temperature (RT) for 90 min.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study revealed that TGF-b regulates iTreg and Th17 cell differentiation by both Smad3-and TAK1dependent pathways in OVA-induced airway inflammation (32). Conversely, evidence suggests the involvement of Hsp, including Hsp70, in the development of psoriasis, characterized by impaired immunological cell function with altered Th17/Treg balance, autoreactive T cells, and dysregulation of keratinocyte proliferation (33,34). Furthermore, Dnajb1 controls the substrate targeting HSP70 (35), and Dnajb1 overexpression downregulates Th17 differentiation in mouse spleen lymphocytes (36).…”
Section: Discussionmentioning
confidence: 99%